2023
DOI: 10.2147/jhc.s411748
|View full text |Cite
|
Sign up to set email alerts
|

Population Sensitive to Lenvatinib Plus Anti-PD-1 for Unresectable Hepatocellular Carcinoma Infected with Hepatitis B Virus

Abstract: Background We explore the dose–efficacy relationship of lenvatinib plus anti-PD-1 in patients with unresectable hepatocellular carcinoma (u-HCC) infected with hepatitis B virus (HBV) in real-world practice. Furthermore, we identify the population sensitive to lenvatinib plus anti-PD-1 treatments. Methods This retrospective study included 70 patients treated with lenvatinib plus at least 3 cycles of anti-PD-1 and 140 with lenvatinib alone. Stabilized inverse probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The duration of lenvatinib was a protective factor of OS. In addition, the Subpopulation Treatment Effect Pattern Plot (STEPP) analysis showed that with the increase of anti-PD-1 treatment cycle, the 12-month survival rate increased slowly, and patients who had been treated with anti-PD-1 for more than five cycles may benefit most from the combined treatment ( 40 ). In other research studies, lenvatinib has demonstrated its ability to inhibit FGFR1–3 signaling and reduce cancer stem-like cells in HCC ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of lenvatinib was a protective factor of OS. In addition, the Subpopulation Treatment Effect Pattern Plot (STEPP) analysis showed that with the increase of anti-PD-1 treatment cycle, the 12-month survival rate increased slowly, and patients who had been treated with anti-PD-1 for more than five cycles may benefit most from the combined treatment ( 40 ). In other research studies, lenvatinib has demonstrated its ability to inhibit FGFR1–3 signaling and reduce cancer stem-like cells in HCC ( 13 ).…”
Section: Discussionmentioning
confidence: 99%